2017
DOI: 10.1111/nep.13007
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with nebivolol attenuates level and expression of matrix metalloproteinases in a rat model of renal ischaemia–reperfusion injury

Abstract: Nebivolol attenuated IRI by decreasing the expression and level of MMP-2 and MMP-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…Previous studies have indicated that nebivolol elicited protection against IR injury in different organs and tissues 12‐15 . To the best of our knowledge, the present study is the first in the literature showing the protective effect of nebivolol on rat urinary bladder contractile dysfunction caused by IR injury.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies have indicated that nebivolol elicited protection against IR injury in different organs and tissues 12‐15 . To the best of our knowledge, the present study is the first in the literature showing the protective effect of nebivolol on rat urinary bladder contractile dysfunction caused by IR injury.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have indicated that nebivolol elicited protection against IR injury in different organs and tissues. [12][13][14][15] To the best of our knowledge, the present study is the first in the literature showing the protective effect of nebivolol on rat urinary bladder contractile dysfunction caused by IR injury. Although therapeutic doses of nebivolol used in the animal models of hypertension range from 5 to 10 mg/kg, lower doses (0.3-2 mg/kg) have also been found to be protective against IR injury.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…CAR and NEB were both shown to inhibit the activity of various MMPs in conditions of enhanced oxidative stress related to atherosclerosis, myocarditis, periodontitis, hypertension, or renal IR injury [11][12][13]15,16]. However, there were no data on the effect of these drugs on MMP activation in acute IR injury of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol (NEB) is a third generation, highly selective β1-adrenoceptor antagonist endowed with the ability to induce nitric oxide release from the endothelium [14]. Moreover, it was shown to attenuate MMP-2 and MMP-9 activities in experimental renovascular hypertension and renal IR injury [15,16]. In contrast, metoprolol (MET) represents a second generation, selective β1-adrenoceptor antagonist with no pleiotropic actions disclosed.…”
Section: Introductionmentioning
confidence: 99%